2017
DOI: 10.1021/acs.jpcc.7b05362
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Hydrated Gibbsite and Brucite Edge Surfaces: DFT Results and Further Development of the ClayFF Classical Force Field with Metal–O–H Angle Bending Terms

Abstract: Molecular scale understanding of the structure and properties of aqueous interfaces with clays, metal (oxy-) hydroxides, layered double hydroxides, and other inorganic phases is strongly affected by significant degrees of structural and compositional disorder of the interfaces. ClayFF was originally developed as a robust and flexible force field for classical molecular simulations of such systems (Cygan, R. T.; Liang, J.-J.; Kalinichev, A. G. J. Phys. Chem. B 2004, 108, 1255–1266). However, despite its success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 82 publications
5
112
0
1
Order By: Relevance
“…64 The interatomic interactions for the montmorillonite were obtained from the CLAYFF 62 force field, and the parameters for the broken edge sites were obtained from newly developed metal-O-H bending potentials consistent with ClayFF. 65,66 The CO 2 and CH 4 molecules were represented by the EPM2 67 and TraPPE-UA 68 models, respectively. Three-dimensional periodic boundary conditions were employed with a cutoff of 14.0 Å for short-range non-electrostatic interactions, and the long-range electrostatic interactions were computed using the particleparticle particle-mesh (PPPM) summation algorithm 69 with an accuracy of 10 À6 .…”
Section: Methodsmentioning
confidence: 99%
“…64 The interatomic interactions for the montmorillonite were obtained from the CLAYFF 62 force field, and the parameters for the broken edge sites were obtained from newly developed metal-O-H bending potentials consistent with ClayFF. 65,66 The CO 2 and CH 4 molecules were represented by the EPM2 67 and TraPPE-UA 68 models, respectively. Three-dimensional periodic boundary conditions were employed with a cutoff of 14.0 Å for short-range non-electrostatic interactions, and the long-range electrostatic interactions were computed using the particleparticle particle-mesh (PPPM) summation algorithm 69 with an accuracy of 10 À6 .…”
Section: Methodsmentioning
confidence: 99%
“…Thus the distribution of internal hydrogen atoms, fundamental for adsorption studies and the description of hydrated imogolites, is best described by the extended CLAYFF model. This aspect has been recently studied by Pouvreau et al 28 that similarly showed the necessity of a M-O-H bending term to properly describe basal and edge surfaces of gibbsite and brucite. From here on, we will 9 use exclusively the extended CLAYFF force field.…”
Section: Resultsmentioning
confidence: 96%
“…4B ) near (5-coordinated) Al atoms at the edge (i.e., this peak is aligned with the first peak on the density profile of Ow-Al(Edge)). The adsorption of a water molecule to form a complete octahedral (6-coordinated) shell about each edge Al atom is expected 24 . The second peak at 2.75 Å is associated with the interaction of O w with the surface hydroxyl O and H atoms denoted OH-2 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous quantum mechanical simulations tried to address this issue by studying the stability 17 , 18 and acid-base properties of clay edge surfaces 19 22 . At the molecular level, one of the most widely used force fields to describe water-clay mineral systems (i.e., ClayFF 23 ) was initially developed to simulate the interaction of water with unreactive basal surfaces and interlayers of layered minerals, but the applicability of ClayFF to edge surfaces has only recently been investigated 24 – 26 . Consequently, the majority of MD simulation studies of clay-water systems have been carried out using a simple slit-shape pore without considering edge effects 13 , 15 , 17 , 27 32 .…”
Section: Introductionmentioning
confidence: 99%